John Constantine, Hellblazer : Shoot - Ellis, Warren; Macan, Darko; Aaron, Jason; Gibbons, Dave, 1949-; Delano, Jamie; Azzarello, Brian; Milligan, Peter; Miéville, China (DC Comics/Vertigo, 2014)
"An assortment of Hellblazer stories written by Brian Azzarello (100 Bullets), Warren Ellis (Planetary), and others. In these stories by some of comics' top writers, John Constantine faces school violence, a desperate, occult family, and more. Plus: A group of documentary filmmakers try to find out what happened to Mucous Membrane - an up-and-coming punk band led by John Constantine that met a mysterious end. Collects Hellblazer #144, 145, 245-246, 250, and Vertigo Resurrected: Hellblazer - Shoot #1"--